2011
DOI: 10.1111/j.1439-0310.2011.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

African Wild Dogs as a Fugitive Species: Playback Experiments Investigate How Wild Dogs Respond to their Major Competitors

Abstract: It has been suggested that African wild dogs Lycaon pictus need exceptionally large home ranges (and hence occur at such low densities) because they are limited by competition with larger sympatric carnivores, namely lions Panthera leo and spotted hyenas Crocuta crocuta. To investigate this relationship at a proximate level and explore which factors mediate it, we conducted audio playback experiments examining how wild dogs responded to the simulated proximity of either lions or hyenas. The principle finding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 44 publications
3
40
1
1
Order By: Relevance
“…Additionally, daily activity data presented by Saleni et al [63] showed that wild dogs in HiP are primarily active during periods of low hyena activity, suggesting that wild dogs in HiP temporally avoid interacting with hyenas at this time scale. Other studies, however, have found little effect of hyenas on wild dogs [51], [64], [65]. The space use results of this study provided no evidence of wild dogs avoiding hyenas either spatially or temporally.…”
Section: Discussioncontrasting
confidence: 81%
“…Additionally, daily activity data presented by Saleni et al [63] showed that wild dogs in HiP are primarily active during periods of low hyena activity, suggesting that wild dogs in HiP temporally avoid interacting with hyenas at this time scale. Other studies, however, have found little effect of hyenas on wild dogs [51], [64], [65]. The space use results of this study provided no evidence of wild dogs avoiding hyenas either spatially or temporally.…”
Section: Discussioncontrasting
confidence: 81%
“…(Laurenson et al 1995, Mills and Gorman 1997, Gorman et al 1998. Playback experiments have for example revealed short-term behavioral modifications in response to the presence of lions and hyenas such as reduced hunting activity and fleeing behavior (Durant 2000, Webster et al 2011, and simulation models revealed the sensitivity of wild dog populations to lion predation (Vucetich and Creel 1999).…”
Section: Portion Of Activity (%)mentioning
confidence: 99%
“…Attracting unwanted attention can potentially be deadly. Larger predators often kill smaller competitor species and playbacks of African wild dog vocalisation have shown that lion actively move towards their location [40], while African wild dogs move away from lion calls [41]. Considering the vulnerability of cheetah to a range of predators it is unlikely that long periods of vocalisation are used for long distance communication and the chirping sound carries far less than lion roars [21] or wolf howls [42].…”
Section: Resultsmentioning
confidence: 99%